APLIKASI PUPUK ORGANIK KASCING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L.) - Gustian, Ulvi; Adiwirman; Nurbaiti (UIR Press, 2025)
Green mustard (Brassica juncea L.) is a high-value vegetable commodity widely favored by the Indonesian population. However, its cultivation on marginal lands, such as inceptisol, is limited due to low soil fertility. This study aimed to evaluate the effect of different doses of vermicompost (kascing) organic fertilizer on the growth and yield of green mustard and to determine the optimal dosage. The research was conducted at the Experimental Farm of the Faculty of Agriculture, University of Riau, from December 2024 to January 2025 using a Completely Randomized Design (CRD) with six treatment levels of kascing (0, 2.5, 7.5, 12.5, 17.5, and 22.5 tons ha⁻¹) and four replications. Observed parameters included plant height, number of leaves, leaf length and width, fresh weight, marketable fresh weight, and dry weight. The results showed that the application of kascing significantly affected all growth and yield parameters. The highest dose of 22.5 tons ha⁻¹ produced the best results in all observed variables, including plant height (29.79 cm), number of leaves (7.8), leaf length (27.50 cm), leaf width (10.19 cm), fresh weight (52.40 g), marketable fresh weight (42.55 g), and dry weight (13.77 g). Based on these findings, it is recommended to apply 22.5 tons ha⁻¹ of kascing to achieve optimal growth and yield of green mustard.